APOYO SOCIAL Y ESTRÉS ACADÉMICO, EN ESTUDIANTES DE CUARTO Y QUINTO SEMESTRE DE LA CARRERA DE PSICOLOGÍA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO. - MOROCHO ROSADO ALEXANDRA PAOLA (2024)
The present research focuses on analyzing the relationship between the variables of social support and academic stress in fourth and fifth semester students of Psychology at Universidad Técnica de Babahoyo. Social support is defined as the network of emotional and material resources that provide backing in stressful situations, enhancing the overall well-being of the individual, while academic stress encompasses the tensions arising from the demands of the educational environment, potentially impacting student performance and mental health negatively. The total population of the study comprises 159 students, with a sample of 88 selected through simple random probabilistic sampling. Employing a quantitative correlational approach and a non-experimental, cross-sectional design, psychometric techniques were applied using the SISCO Academic Stress Inventory, developed by Barraza in 2007, and the Multidimensional Scale of Perceived Social Support (MSPSS), created by Zimet, Dahlem, Zimet, and Farley in 1988. The results of the correlation analysis revealed a Spearman coefficient of 0.210, indicating a slight positive correlation between perceived social support and academic stress. However, the p-value of 0.975 with 86 degrees of freedom did not reach statistical significance, suggesting that the observed association could be due to chance or unconsidered variables in this study. Therefore, although there is a tendency towards higher levels of academic stress with greater perception of social support, there was insufficient evidence to assert a clear and significant correlation in this specific group of students.